ASPIRE Consensus on the Structure of Care in Endometriosis - Networks of Expertise - Siriruthai Amnatbuddee; Neil P. Johnson; Deborah Bush; Angela Aguilar; Clare Boothroyd; Praveen De Silva; Loula George; Jane E. Girling; Elizabeth Glanville; Teresa Gudex; M. Louise Hull; Rebecca Kerner; et al. (Fertility & Reproduction)
Background: Effective management of endometriosis necessitates a comprehensive, multidisciplinary approach. Networks or centres of expertise play a pivotal role in enhancing clinical care, fostering collaboration, and promoting innovative research, knowledge dissemination, and healthcare professional training. Despite the established benefits of structured care systems, there remains no global consensus on the essential components of an endometriosis network of expertise. This study aims to define key elements for such networks, with a particular focus on improving care structures in the Asia-Pacific region. Methods: A three-stage consensus process was conducted by Asia Pacific Initiative on Reproduction (ASPIRE), incorporating literature review, modified Delphi surveys, and face-to-face and virtual consensus meetings. The process involved multidisciplinary stakeholders, including medical and paramedical professionals, researchers, patients and patient advocates. Two rounds of Delphi surveys refined key features based on stakeholder input, followed by consensus refinement through a face-to-face consensus development meeting at the ASPIRE Auckland Endometriosis Masterclass 2024, a subsequent Zoom meeting, then specific patient and patient advocate input to finalise the key features. Results: Consensus was reached on 38 key features, categorised into five domains: network importance, organisational structure, clinical services, training and research. The study highlights the strength of a multidisciplinary approach, ensuring accessibility to specialised surgical, pain management and fertility services, with the person with endometriosis at the centre of this structure. The inclusion of experts in acupuncture, nutrition, psychology, physiotherapy and other allied health fields enhances patient care through a multidisciplinary holistic care approach, addressing the diverse needs of individuals with endometriosis. Conclusions: Consensus has been reached on key features of an endometriosis network of expertise, incorporating the perspectives of those with lived experience and their advocates, to improve endometriosis care across the Asia-Pacific region. This framework serves as a reference for global discussions. It has the potential to become an audit accreditation standard in Asia-Pacific.